Review of the epidemiology, diagnosis and management of invasive meningococcal disease in Vietnam - Phung Nguyen The Nguyen; Nguyen Thanh Hung; Gaurav Mathur; Thatiana de Jesus Pereira Pinto; Nguyen Hoan Le Minh (Taylor & Francis Group, 2023)
Invasive meningococcal disease (IMD), caused by Neisseria meningitidis, is life-threatening with a high case fatality rate (CFR) and severe sequelae. We compiled and critically discussed the evidence on IMD epidemiology, antibiotic resistance and disease management in Vietnam, focusing on children. PubMed, Embase and gray literature searches for English, Vietnamese and French publications, with no date restrictions, retrieved 11 eligible studies. IMD incidence rate (/100,000 population) was 7.4 [95% confidence interval 3.6-15.3] in children under 5 years of age; driven by high rates in infants (e.g. 29.1 [8.0-106.0] in 7-11 month-olds). Serogroup B IMD was predominant. Neisseria meningitidis strains may have developed resistance to streptomycin, sulfonamides, ciprofloxacin, and possibly ceftriaxone. There was a lack of current data on diagnosis and treatment of IMD, which remain challenging. Healthcare professionals should be trained to rapidly recognize and treat IMD. Preventive measures, such as routine vaccination, could help address the medical need.